How Do Intergenerational Economic Support, Emotional Support and Multimorbidity Affect the Catastrophic Health Expenditures of Middle-Aged and Elderly Families?–Evidence From CHARLS2018 - Tang, Shaoliang; Yao, Ling; Li, Zhengjun; Yang, Tongling; Liu, Meixian; Gong, Ying; Xu, Yun; Ye, Chaoyu (Frontiers in Public Health, 2022)
Abstract Objectives: The elderly face multiple vulnerabilities such as health, economy and society, and are prone to catastrophic health expenditures. This study aims to analyze the impact of children's intergenerational economic support, emotional support, and illness on the catastrophic health expenditures of middle-aged and elderly families. Methods: Using China Health and Retirement Longitudinal Study (CHARLS 2018) data to calculate the catastrophic health expenditure of Chinese households as the dependent variable. Taking children’s intergenerational economic support, emotional support and multimorbidity as core independent variables, gender, age, marital status, medical insurance and other variables as control variables, and perform logistic regression analysis. According to the heterogeneity analysis of age and gender, the impact of intergenerational economic support, emotional support and multimorbidity on the catastrophic health expenditure of middle-aged and elderly families is explored. Results: When catastrophic health expenditures occur in middle-aged and elderly families, the children’s intergenerational economic support will increase significantly, especially in families with members aged 60-74. Children’s emotional support can effectively reduce the risk of catastrophic health expenditures for middle-aged and elderly families. Compared with children’s intergenerational economic support and emotional support, the impact of multimorbidity on the catastrophic health expenditures of middle-aged and elderly families is the most significant. Suffering from multimorbidity can increase the risk of catastrophic health expenditures for middle-aged and elderly families, especially families with male members suffering from multiple diseases. Conclusions: It is recommended that we should do a good job in popularizing the knowledge of chronic diseases to minimize the occurrence of multimorbidity. The government should establish group medical insurance related to chronic disease diagnosis. According to the severity of the disease or the special circumstances of the patient, the level of medical insurance reimbursement is divided in detail, especially for chronic disease clinics and drug reimbursement. Children should be encouraged to strengthen the emotional connection and effective care of the elderly, focusing on the elderly 60-74 years old, in order to reduce their care pressure and maintain the physical and mental health of the elderly.